Durability of the moderate-to-heavy intensity transition can be predicted using readily available markers of physiological decoupling - Jeffrey A. Rothschild; Gabriele Gallo; Kate Hamilton; Julian D. Stevenson; Harrison Dudley-Rode; Thanchanok Charoensap; Daniel J. Plews; Andrew E. Kilding; Ed Maunder (European Journal of Applied Physiology, 2025)
Purpose To assess relationships between heart rate (HR), ventilation (̇ $$\dot V$$ V ˙ E ), and respiratory frequency (F R ) decoupling and durability of the first ventilatory threshold (VT 1 ), and the strength of practical models to predict power output at VT 1 during prolonged exercise. Methods Durability of VT 1 was assessed via measurements of power output at VT 1 before and after ~ 2.5-h of initially moderate-intensity cycling in 51 trained cyclists, as part of four studies published elsewhere. In 12 of those participants, power output at VT 1 was assessed every hour until task failure. For every assessment of power output at VT 1 , HR, F R , and $$\dot V$$ V ˙ ̇ E was measured at fixed power outputs, and thus decoupling of these variables with power output was determined. Bivariate repeated-measures correlations (r rm ) between decoupling and durability of VT 1 were assessed. Multivariable models were created to predict power output at VT 1 during prolonged exercise using generalised estimating equations. Results Negative correlations were observed between exercise-induced change in power output at VT 1 and HR (r rm = −0.76, P < 0.001) and F R (r rm = −0.40, P = 0.013) decoupling, but not $$\dot V$$ V ˙ ̇ E decoupling (r rm = −0.25, P = 0.136). The final prediction model, containing baseline VT 1 and peak oxygen uptake, F R decoupling, and an interaction between HR decoupling and exercise duration, effectively predicted real-time VT 1 (mean absolute error, ~ 7.2 W; R 2 , 0.95). Conclusion HR and/or F R decoupling during controlled training sessions may be a practically useful durability assessment. Our prediction models may be an effective means of improving within-session intensity regulation and training load monitoring.

Carbohydrate ingestion during prolonged exercise blunts the reduction in power output at the moderate-to-heavy intensity transition - Harrison Dudley-Rode; Caryn Zinn; Daniel J. Plews; Thanchanok Charoensap; Ed Maunder (European Journal of Applied Physiology, 2025)